Fatimid expansion in the regions of Tripoli, the West and Cyrenaica, and the attitude of the people towards it - الأحمر, رمضان (Scientific Journal of University of Benghazi, 2021)
After the success of the Fatimids in defeating the Aghlabids rulers in the Morocco of nearer (Ifriqiya) and the establishment of their Shiite state on their lands in the year 297 AH / 909 CE. Their expansion ambitions began to move towards the East, specifically to Egypt. In order to reach it, they had to first impose their control over the provinces of Tripoli of-the-West and Barca and to submit their people to their authority, to be the way ahead of them to Egypt will be safe and passable. In this paper, we aim to clarify the picture of the Fatimid expansion in the Tripoli of-the-West and Barca and clarify the position of the people of the two provinces from it and how they deal with Fatimid presence. Moreover, by using, a historical method that depends on retrieving historical information related to the period of study, then collection it, scrutinize it, analyze it and compare it in some cases, and then write in a proper historical manner. The study was able to achieve its goals by knowing the steps taken by the Fatimids to complete their expansion at the two provinces and success in control it. In addition, it has managed to clarify the stance of the people of the two provinces regarding this expansion and control. That stance, often characterized by the spirit of resistance and rebellion. Furthermore, the study concluded that the inhabitants of the two provinces and its people did not submit to the rule and authority of the Fatimids except by force of arms, and after several revolts from them, the Fatimids were able to suppress it with iron and fire. Moreover, that this submission was political only, so the Fatimids could not subject them to their doctrine, as the Shiite sect did not find acceptance and spread among the inhabitants of the two provinces.